Evaluation of Student Learning in Remotely Controlled Instrumental Analyses - Meintzer, Chris; Sutherland, Frances; Kennepohl, Dietmar (International Review of Research in Open and Distributed Learning, 2017)
The Canadian Remote Sciences Laboratories (CRSL) website (www.remotelab.ca) was successfully employed in a study of the differences in the performance and perceptions of students’ about their learning in the laboratory (in-person) versus learning at a remote location (remote access). The experiment was completed both in-person and via remote access by 70 students, who performed essentially the same, academically, in the two modes. One set of students encountered the in-person laboratory first and then did the remote laboratory, while the other set of students did the activities in the reverse order. The student perception survey results (n = 46) indicated that the students found both experimental scenarios to be at appropriate levels of difficulty, clear to understand, and did not overall prefer one way of completing the experiment over the other. However, they felt that they learned more about the theory of the experiment, more hands-on skills, and more about the operation of the instrument when they performed the experiment in the laboratory in the presence of an instructor. They also believed that they learned more about the instrument operation from their laboratory partner when they completed the experiment in the laboratory, but learned more from their partner about the operation of the instrument software when they completed the procedure from a remote location.